Correction: Development of a strawberry transpiration model based on a simplified Penman–Monteith model under different irrigation regimes - Ha Seon Sim; Jung Su Jo; Yu Hyun Moon; Soo Bin Jung; Tae Yeon Lee; Ha Rang Shin; Yong Jun Kim; Na Kyong Kim; Sung Kyeom Kim (Horticulture, Environment, and Biotechnology, 2026)

Prediction and application on the first flowering date of June-bearing strawberry cultivars using Ensemble-based Machine learning with primary temperature values - Tae Yeon Lee; Yu Hyun Moon; Ha Seon Sim; Soo Bin Jung; Ui Jeong Woo; Ha Rang Shin; Yong Jun Kim; Na Kyoung Kim; Jung Su Jo; Sung Kyeom Kim (Computers and Electronics in Agriculture, 2026)

Development of a strawberry transpiration model based on a simplified Penman–Monteith model under different irrigation regimes - Ha Seon Sim; Jung Su Jo; Yu Hyun Moon; Soo Bin Jung; Tae Yeon Lee; Ha Rang Shin; Yong Jun Kim; Na Kyong Kim; Sung Kyeom Kim (Horticulture, Environment, and Biotechnology, 2025)

Novel method for crop growth tracking with deep learning model on an Edge Rail Camera - Seungwoo Kum; Jaewon Moon; Seungtaek Oh; Hyun Kwon Suh; Hyeonji Park; Ha Seon Sim; Jung Su Jo; Sung Kyeom Kim; Seungwook Choi; Francisco Andres Pérez (Computers and Electronics in Agriculture, 2025)

Determination of LEDs arrangement in a plant factory using a 3D ray-tracing simulation and evaluation on growth of Cucurbitaceae seedlings - Hye Jin Lee; Yu Hyun Moon; Sewoong An; Ha Seon Sim; Ui Jeong Woo; Hyunseung Hwang; Sung Kyeom Kim (Horticulture, Environment, and Biotechnology, 2023)

Correction to: Prediction of strawberry fruit yield based on cultivar-specific growth models in the tunnel-type greenhouse - Jung Su Jo; Dong Sub Kim; Won Jun Jo; Ha Seon Sim; Hye Jin Lee; Yu Hyun Moon; Ui Jeong Woo; Soo Bin Jung; Steven Kim; Xiaoming Mo; Su Ran Ahn; Sung Kyeom Kim (Horticulture, Environment, and Biotechnology, 2023)

Prediction of strawberry fruit yield based on cultivar-specific growth models in the tunnel-type greenhouse - Jung Su Jo; Dong Sub Kim; Won Jun Jo; Ha Seon Sim; Hye Jin Lee; Yu Hyun Moon; Ui Jeong Woo; Soo Bin Jung; Steven Kim; Xiaoming Mo; Su Ran Ahn; Sung Kyeom Kim (Horticulture, Environment, and Biotechnology, 2022)
The strawberry growth and fruit yield of five Korean cultivars in the tunnel-type greenhouse predicted using their growth. The number of leaves, petiole length, leaf length and width, crown diameter, and the ratio of red and far-red (RFR) of the five Korean cultivars were measured during the cultivation period. The number of leaves of all cultivars exhibited a similar trend during this period; the plant and petiole length of ‘Maehyang’ were the longest, leaf length exhibited similar trends in all five cultivars except for ‘Jukhyang’, the leaf width of ‘Arihyang’, was the longest, and crown diameter of ‘Keumsil’ was the thickest. The leaf length, crown diameter, and RFR were associated with the fruit yield in the multiple linear regression. When a single model was used to predict the yield of all five cultivars, the correlation between expected yield and actual yield was r = 0.53. When cultivar-specific models were built for the prediction, the correlation increased to r = 0.77. The results indicated that the fruit yield of strawberry cultivars could be better predicted by considering cultivar-specific information, so it may be necessary to consider individual cultivars specifically rather than all cultivars simultaneously.